The Role of the DPRD in Maximizing the Regional Design Concerning the Management of Regional Property for the Welfare of the People of North Sumatra - Fatwa Nasya Al Hadi; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
The focus of this research is on the role of the DPRD of North Sumatra for the draft for the formation of regional regulations in 2022 regarding regional property for the welfare of the community. In accordance with the Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government and Government Regulation Number 27 of 2014 concerning Management of State/Regional Property and Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for Management of Regional Property. Regional Property must be managed properly and correctly. The research was conducted using a qualitative approach. The informants studied were information from members of the DPRD of North Sumatra, staff and management of the DPRD of North Sumatra. The results of the study indicate that the draft Regional Regulation on the Management of Regional Property, starting from the review process in accordance with Pancasila and the 1945 Constitution, referring to and guided by the provisions of the statutory hierarchy, prioritizing the welfare of the community, to increasing, accelerating development in North Sumatra Province. Regional Property Management includes 3 (three) main functions, namely proper planning, efficient and effective implementation/utilization and monitoring (monitoring). In order for these three functions to be achieved, the right strategy is needed in the management of Regional Property.